R&D Tahap Assesment: Keefektifan Bahan Ajar Statistik Pendidikan Berbasis LC 5E Berbantu Minitab - Abdillah, Agus; Prasetyono, Hendro; Rizkiyah, Nur; Fitria, Dona; Burhanudin, Burhanudin (Universitas Indraprasta PGRI, 2021)
One indicator that learning can be said to be effective is optimal learning outcomes. In fact, to achieve the word